Japanese cancer patient participation in and satisfaction with treatment-related decision-making: A qualitative study - Takahashi Miyako; Watanabe Yoshiko; Kai Ichiro (BMC, 2008)
Abstract Background Over the last decade, patient involvement in treatment-related decision-making has been widely advocated in Japan, where patient-physician encounters are still under the influence of the long-standing tradition of paternalism. Despite this profound change in clinical practice, studies investigating the actual preferences of Japanese people regarding involvement in treatment-related decision-making are limited. The main objectives of this study were to (1) reveal the actual level of involvement of Japanese cancer patients in the treatment-related decision-making and their overall satisfaction with the decision-making process, and (2) consider the practical implications of increased satisfaction in cancer patients with regard to the decision-making process. Methods We conducted semi-structured interviews with 24 Japanese cancer patients who were recruited from a cancer self-help group in Tokyo. The interviews were qualitatively analysed using the approach described by Lofland and Lofland. Results The analyses of the patients' interviews focused on 2 aspects: (1) who made treatment-related decisions (the physician or the patient), and (2) the informants' overall satisfaction with the decision-making process. The analyses revealed the following 5 categories of decision-making: 'patient as the active decision maker', 'doctor selection', 'wilfully entrusting the physician', 'compelled decision-making', and 'surrendering decision-making'. While the informants under the first 3 categories were fairly satisfied with the decision-making process, those under the latter 2 were extremely dissatisfied. Informants' views regarding their preferred role in the decision-making process varied substantially from complete physician control to complete patient control; the key factor for their satisfaction was the relation between their preferred involvement in decision-making and their actual level of involvement, irrespective of who the decision maker was. Conclusion In order to increase patient satisfaction with regard to the treatment-related decision-making process, healthcare professionals in Japan must assess individual patient preferences and provide healthcare accordingly. Moreover, a better environment should be created in hospitals and in society to facilitate patients in expressing their preferences and appropriate resources need to be made available to facilitate their decision-making process.